Digestibility Value and Fermentation Level of Local Feed-Based ration for Sheep - Mayulu, Hamdi; Fauziah, N; Christiyanto, M; Sunarso, Sunarso; Haris, M I (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2018)
Feed Digestibility is an important indicator which can be used as a guideline to determine the amount of nutrient and feed that can be absorbed by digestive tract. The objective of the research was to determine the value dry matter digestibility (DMD), organic matter digestibility (OMD), NH3 fermentation level and volatile fatty acid (VFA) fermentation level. The research was conducted on January 2018 in Animal Feed and Nutrition Laboratory of Animal Husbandry and Agriculture Faculty, Diponegoro University Semarang. The research method used was in vitro analysis with complete randomized design with five treatments and four replicates. The data were analyzed with analysis of variance at 95% significant level, followed by Duncan Multiple Range Test. The results showed that the highest score of DMD was T5=56.51±0.33%, T4=56.41±2.11; T3=55.86±0.83; highest score of OMD was T5=62.48±0.39%, T4=61.87±1.60; T3=60.86±1.10, the highest NH3 concentration was T3=6.07±1.55 mM, and the highest VFA concentration was T5=55.25±3.40 mM. Sheep’s local feed-based ration was significantly (P<0.05) influenced in vitro DMD, OMD, NH3 fermentation level and VFA fermentation level